Pneumonia or tuberculosis? A case report in a teenage girl - Zapolnik, Paweł; Pogorzelski, Andrzej; Zapolnik, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Tuberculosis (TB) is still a common infectious disease worldwide. In 2018, seven million new cases of TB were reported to the World Health Organization. The diagnosis of TB in children is difficult due to non-characteristic symptoms. A 14-year-old girl presented to a general practitioner due to coughing and general weakness for three weeks. Physical examination revealed a reduction in vesicular murmur over a significant area of the right lung, and chest X-ray showed extensive densities in the right lung. After several days of hospitalisation and antibiotic therapy for bacterial pneumonia, the girl was diagnosed with TB. A treatment plan was applied for six months. Radiological and clinical improvement was observed after the therapy. A detailed history, determining contact with the TB patient, physical examination, results of additional tests, and broad-spectrum antibiotics response are essential for diagnosis.